Sources of Infection Among Confirmed Cases of COVID-19 in Jeju Province, Korea - Moonkyong Hwang; Jong-Myon Bae (Korean Society for Preventive Medicine, 2021)
Objectives Jeju Province in Korea reported 627 coronavirus disease 2019 (COVID-19) cases between January 20, 2020, and March 31, 2021. This study analyzed the sources of infection among confirmed cases in Jeju Province, a self-governed island. Methods The sources of infection were broadly categorized as follows: (1) infections from overseas (confirmed patients who reported travel overseas or contact with overseas travelers); (2) infections from outside Jeju Province (confirmed patients who had visited other provinces or had contact with individuals who had traveled to other provinces in Korea); and (3) unknown sources of infection (confirmed patients who were infected following contact with an infected person whose source of infection was unknown). The chi-square test was used to analyze the differences in the distributions of related variables for each source of infection. Results Of the 627 confirmed cases, 38 (6.1%) were infections from overseas sources, 199 (31.7%) were from outside of Jeju Province, and 390 (62.2%) were from unknown sources. Jeju Province had no cases with an unknown source of infection during the first and second waves of the nationwide outbreak. Conclusions Infections from overseas sources could be blocked from spreading to local communities in Jeju Province by conducting screening at the airport, along with the preemptive suspension of visa-free entry. In addition, considering the scale of the nationwide outbreak, measures must be established to delay outbreaks from unknown sources of infection caused by sources outside Jeju Province.